2021
DOI: 10.21037/atm-20-731
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for pyrrolizidine alkaloid-induced hepatic sinusoidal obstruction syndrome: a multicenter study in China

Abstract: Background: In China, one of the major causes of hepatic sinusoidal obstruction syndrome (HSOS) is the intake of herbals containing pyrrolizidine alkaloid (PA). However, prognostic factors for PA-induced HSOS are poorly understood. The aim of this study was to identify the independent prognostic factors for PAinduced HSOS using a multi-center study. Methods: A total of 117 PA-induced HSOS patients were enrolled for data collection in three university hospitals from November 2003 to September 2018. Univariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Of 91 patients, 80 patients (87.91%) received symptomatic therapy containing the termination of PAs exposure, symptomatic treatment, hepatoprotective drugs (symptomatic group) and 11 patients (12.09%) received anticoagulation therapy containing LMWH plus symptomatic therapy (LMWH group). Our study and previous studies demonstrated a cumulative survival rate of 6, 12 and 36 months were similar in patients with PAs‐induced HSOS 10,11,14 ; thus, survival patients with a minimum follow‐up period of 1 year were enrolled in our study. Table 1 summarized relevant demographic and clinical biochemistry at the time of baseline evaluation.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Of 91 patients, 80 patients (87.91%) received symptomatic therapy containing the termination of PAs exposure, symptomatic treatment, hepatoprotective drugs (symptomatic group) and 11 patients (12.09%) received anticoagulation therapy containing LMWH plus symptomatic therapy (LMWH group). Our study and previous studies demonstrated a cumulative survival rate of 6, 12 and 36 months were similar in patients with PAs‐induced HSOS 10,11,14 ; thus, survival patients with a minimum follow‐up period of 1 year were enrolled in our study. Table 1 summarized relevant demographic and clinical biochemistry at the time of baseline evaluation.…”
Section: Resultsmentioning
confidence: 57%
“…The intake of PAs-containing medicinal herbs is one of the major etiologies of HSOS. 3,8,10,14,[21][22][23][24][25] Definitive treatment for PAs-induced HSOS is not available in clinical practice. 3,4 Our study demonstrated enoxaparin, an anticoagulant, improved the prognosis of patients with PAs-induced HSOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings indicate that initial TIPS may provide a greater survival benefit than AT for the management of severe or very severe PA-induced HSOS. Moreover, Shang et al [25] demonstrated that the presence of severe or very severe disease is an independent prognostic factor in patients with PA-induced HSOS and is associated with a higher mortality rate than that of mild or moderate disease. In the present study, all the patients with very severe HSOS and 40% of those with severe HSOS died in the AT group, whereas all the patients survived in the TIPS group.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the rst diagnostic criteria and treatment strategy for PA-HSOS were proposed 7 . Anticoagulation-transjugular intrahepatic portosystemic shunt (TIPS) stepwise therapy (anticoagulation rst, if no response, step-up to TIPS therapy) is recommended, and this has an increased survival up to 91% 1,[8][9][10][11][12] . However, the exact mechanism of this treatment modality is unclear.…”
Section: Introductionmentioning
confidence: 99%